Leisure education, community development, and populations with special needs - Sivan, A.; Ruskin, H.
This book is a result of an output of Commission of the World Leisure and Recreation Association (WLRA) to examine the role of leisure and education for leisure activities among people with special needs living in the community, requiring social or health services outside hospital. This book provides a conceptual and practical framework for understanding the process of leisure education and its role for community development and populations with special needs. It will serve the reader as a foundation for developing models and programmes for leisure education within community settings and will be of interest to those working and researching in the area of education, leisure and community development